Abstract 12797: Obesity Predisposes Pediatric Cancer Patients Treated With Anthracyclines to Subclinical Cardiac Dysfunction Detectable by Strain Echocardiography - George, Ian A; Souder, BriAnna; Berkman, Amy; Noyd, David; Campbell, Michael J; Barker, Piers; Roth, Michael; HILDEBRANDT, Michelle; Oeffinger, Kevin C; Landstrom, Andrew P; McCrary, Andrew (Circulation (New York, N.Y.), 2022)
IntroductionAnthracyclines are used in > 60% of pediatric cancer cases yet are associated with a life-long risk of cardiomyopathy. Strain echocardiography is currently the standard of care for cardiac surveillance in adult cardio-oncology. However, strain has yet to be widely evaluated in the pediatric population. HypothesisStrain analysis on echocardiograms from anthracycline-exposed pediatric patients will identify dysfunction that is overlooked by left ventricular ejection fraction (LVEF) alone and which will be associated with identifiable cardiovascular risk factors. MethodsAll anthracycline-exposed cancer patients < 18 years old with an initial visit to Duke University between 2013-2019 were identified. Subjects with cancer relapses, congenital heart disease, or inadequate imaging for analysis were excluded. Peak longitudinal left ventricular strain was calculated from the 4-chamber view on all adequate surveillance studies for each patient using the TOMTEC AutoSTRAIN software. Univariate and multivariate Cox proportional hazards models were created to identify risk factors for abnormal LVEF (<50%) or abnormal longitudinal strain (>-16%). ResultsThe cohort included 101 subjects (52% male) with 606 echocardiograms for analysis. Median age at diagnosis was 12 years (IQR = 3-15), and median anthracycline dose was 201 mg/m2 (IQR = 120-284). Median follow-up duration was 3.7 years (IQR = 2.3-5.3). Abnormal LVEF was identified in 5 subjects, while abnormal strain was identified in 16 subjects. All subjects with abnormal LVEF also had abnormal strain. When adjusting for dose, BMI, and family history of cardiovascular disease, anthracycline dose > 250 mg/m2 and BMI > 25 at diagnosis were predictors of abnormal strain with hazards ratios of 3.3 (p =.02, CI = 1.2-8.9) and 3.2 (P = .03, CI = 1.1-9.5), respectively. Anthracycline dose was the only significant predictor of abnormal LVEF. ConclusionsLongitudinal strain is more sensitive than LVEF alone in identifying subclinical cardiac dysfunction in pediatric cancer patients, and those with a BMI > 25 at diagnosis are at an increased risk of dysfunction. Multi-center studies should further explore the link between obesity, early subclinical dysfunction, and subsequent cardiomyopathy.